2-Hydroxy-(4-methylseleno)butanoic Acid Is Used by Intestinal Caco-2 Cells as a Source of Selenium and Protects against Oxidative Stress. Issue 12 (28th August 2019) - Campo-Sabariz, Joan; Moral-Anter, David; Brufau, M Teresa; Briens, Mickael; Pinloche, Eric; Ferrer, Ruth; Martín-Venegas, Raquel
ABSTRACT: Background: Selenium (Se) participates in different functions in humans and other animals through its incorporation into selenoproteins as selenocysteine. Inadequate dietary Se is considered a risk factor for several chronic diseases associated with oxidative stress. Objective: The role of 2-hydroxy-(4-methylseleno)butanoic acid (HMSeBA), an organic form of Se used in animal nutrition, in supporting selenoprotein synthesis and protecting against oxidative stress was investigated in an in vitro model of intestinal Caco-2 cells. Methods: Glutathione peroxidase (GPX) and thioredoxin reductase (TXNRD) activities, selenoprotein P1 protein (SELENOP) and gene ( SELENOP ) expression, and GPX1 and GPX2 gene expression were studied in Se-deprived (FBS removal) and further HMSeBA-supplemented (0.1–625 μM, 72 h) cultures. The effect of HMSeBA supplementation (12.5 and 625 μM, 24 h) on oxidative stress induced by H2 O2 (1 mM) was evaluated by the production of reactive oxygen species (ROS), 4-hydroxy-2-nonenal (4-HNE) adducts, and protein carbonyl residues compared with a sodium selenite control (SS, 5 μM). Results: Se deprivation induced a reduction ( P  < 0.05) in GPX activity (62%), GPX1 expression, and both SELENOP (33%) and SELENOP expression. In contrast, an increase ( P  < 0.05) in GPX2 expression and no effect in TXNRD activity ( P  = 0.09) were observed. HMSeBA supplementation increased ( P  < 0.05) GPX activity (12.5–625 μM, 1.68–1.82-fold) and SELENOP protein expression (250 and 625 μM, 1.87- and 2.04-fold). Moreover, HMSeBA supplementation increased ( P  < 0.05) GPX1 (12.5 and 625 μM), GPX2 (625 μM), and SELENOP (12.5 and 625 μM) expression. HMSeBA (625 μM) was capable of decreasing ( P  < 0.05) ROS (32%), 4-HNE adduct (49%), and protein carbonyl residue (75%) production after H2 O2 treatment. Conclusion: Caco-2 cells can use HMSeBA as an Se source for selenoprotein synthesis, resulting in protection against oxidative stress.